2014
DOI: 10.1111/1574-6941.12270
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the composition and diversity of the bacterial microbiota associated with oysters (Crassostrea corteziensis,Crassostrea gigasandCrassostrea sikamea) during commercial production

Abstract: The resident microbiota of three oyster species (Crassostrea corteziensis, Crassostrea gigas and Crassostrea sikamea) was characterised using a high-throughput sequencing approach (pyrosequencing) that was based on the V3-V5 regions of the 16S rRNA gene. We analysed the changes in the bacterial community beginning with the postlarvae produced in a hatchery, which were later planted at two grow-out cultivation sites until they reached the adult stage. DNA samples from the oysters were amplified, and 31 008 sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
66
6
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 69 publications
(146 reference statements)
10
66
6
4
Order By: Relevance
“…However, these bacteria have been previously found in Pacific oysters in Tasmania (Fernandez-Piquer et al, 2012), suggesting their affinity to form associations with oysters. Both Spirochaetes and Tenericutes are commonly isolated from various oyster tissues (Prieur et al, 1990; Green and Barnes, 2010; Husmann et al, 2010; King et al, 2012; Trabal et al, 2012; Wegner et al, 2013; Trabal Fernandez et al, 2014; Lokmer et al, 2016). However, Spirochaetes and Tenericutes are rare in the hemolymph in the laboratory (Lokmer and Wegner, 2015; Lokmer et al, 2016), where high abundance of Tenericutes is mainly linked to stress or even mortality (Lokmer and Wegner, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these bacteria have been previously found in Pacific oysters in Tasmania (Fernandez-Piquer et al, 2012), suggesting their affinity to form associations with oysters. Both Spirochaetes and Tenericutes are commonly isolated from various oyster tissues (Prieur et al, 1990; Green and Barnes, 2010; Husmann et al, 2010; King et al, 2012; Trabal et al, 2012; Wegner et al, 2013; Trabal Fernandez et al, 2014; Lokmer et al, 2016). However, Spirochaetes and Tenericutes are rare in the hemolymph in the laboratory (Lokmer and Wegner, 2015; Lokmer et al, 2016), where high abundance of Tenericutes is mainly linked to stress or even mortality (Lokmer and Wegner, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, spatial and geographic information has so far primarily served to delineate core microbiomes (e.g., King et al, 2012; Wong et al, 2013; Dishaw et al, 2014) or to differentiate between the microbiomes of closely related species (Zouache et al, 2011; Phillips et al, 2012). This applies especially to marine hosts (e.g., Morrow et al, 2012; Reveillaud et al, 2014; Trabal Fernandez et al, 2014). Studies considering aspects of within-species spatial variation are less common and focused on large-scale differences between environmentally distinct sites (e.g., Trabal et al, 2012; Pierce et al, 2016; Ziegler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found Proteobacteria to be the most abundant phylum in freshwater sediments (Bucci et al, 2014; Dai et al, 2016; Wakelin, Colloff & Kookana, 2008; Zeng et al, 2008; Zhang et al, 2015), sediments with mollusks (Fernandez et al, 2014; Lee et al, 2015), and also mollusk microbiomes (Frischer et al, 2000; Neta et al, 2015; Ngangbam et al, 2015; Trabal et al, 2012). Although our results showed Proteobacteria were the most abundant phylum, we observed a decrease in Proteobacteria by 6% and an increase in Nitrospirae by 10% in the presence of mussels.…”
Section: Discussionmentioning
confidence: 99%
“…; Trabal Fernandez et al . ). A similar tendency of lower species richness in the final control group ( t = 30) with respect to the initial control group ( t = 0) was also observed as estimated by Chao‐1, even though oysters remained as juvenile.…”
Section: Discussionmentioning
confidence: 97%
“…In a study with different oyster species, Trabal Fernandez et al . () found that Burkholderia and Escherichia / Shigella were the only Proteobacteria omnipresent in the adult stage of C. sikamea in two different cultivation sites and in the postlarvae stage at the rearing hatchery. Although oysters in this study were in their juvenile stage, the core microbiota of C. sikamea from these two independent studies did not share a single genus.…”
Section: Discussionmentioning
confidence: 99%